INVARIANT PRACTICAL TASKS FOR WORK WITH DATABASES AT THE SECONDARY SCHOOL - Kartashova, L.I.; Levchenko, I.V.; Pavlova, A.E. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
This article provides examples of practical tasks for creating and editing databases for secondary school students. Jobs are invariant in nature and do not depend on specific software tools. This is due to the fact that, at present, information technology and their tools are used almost everywhere, in various spheres of human activity. Therefore, the professional success of modern school graduates who have to live and work in the information society, depends on their ability to timely and correctly use information technology and their means for solving various tasks. This can be achieved when on the lessons of informatics will be examined not specific means of information technology, or specific versions of software that are changing rapidly, but will be implemented a fundamental invariant approach to teaching information technology. To do this it is important to select invariant IT learning content, define the sequence of learning issues, as well as to pick up correctly and logically build jobs that should be invariant relative to software. This approach to teaching information technology will have an impact on the formation of generalized ways of student information activities.